Neural correlates of motor imagery and execution in real-world dynamic behavior: evidence for similarities and differences - Mustile, Magda; Kourtis, Dimitrios; Edwards, Martin G.; Donaldson, David I.; Ietswaart, Magdalena (Frontiers in Human Neuroscience, 2024)
A large body of evidence shows that motor imagery and action execution behaviours result from overlapping neural substrates, even in the absence of overt movement during motor imagery. To date it is unclear how neural activations in motor imagery and execution compare for naturalistic whole-body movements, such as walking. Neuroimaging studies have not directly compared imagery and execution during dynamic walking movements. Here we recorded brain activation with mobile EEG during walking compared to during imagery of walking, with mental counting as a control condition. We asked twenty-four healthy participants to either walk six steps on a path, imagine taking six steps or mentally count from one to six. We found beta and alpha power modulation during motor imagery resembling action execution patterns; a correspondence not found performing the control task of mentally counting. Neural overlap occurred early in the execution and imagery walking actions, suggesting activation of shared action representations.Remarkably, a distinctive walking-related beta rebound occurred both during action execution and imagery at the end of the action suggesting that, like actual walking, motor imagery involves resetting or inhibition of motor processes. However, we also found that motor imagery elicits a distinct pattern of more distributed beta activity especially at the beginning of the task. These results indicate that motor imagery and execution of naturalistic walking involve shared motorcognitive activations, but that motor imagery requires additional cortical resources.